2001
DOI: 10.1021/es0001005
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Selenium in Coal Combustion:  Volatilization and Speciation in the Flue Gas

Abstract: In light of Title I of the Clean Air Act Amendments of 1990, selenium will most probably be considered for regulation in the electric power industry. This has generated interest for removing this element from fossil-fired flue gas. This study deals with coal combustion: selenium volatilization and its speciation in the cooled flue gas were investigated to better understand its chemical behavior to validate the thermodynamic approach to such complex systems and to begin developing emission control strategies. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 11 publications
1
45
1
Order By: Relevance
“…The enrichment of selenium in the diluted PM 2.5 sample is not unexpected, as selenium is present in the gas phase at stack conditions (Germani and Zoller 1988;Galbreath et al 2000;Yan et al 2001). Selenium enrichment has been observed in Figure 1.…”
Section: Dilution and Pm 25 Compositionmentioning
confidence: 60%
“…The enrichment of selenium in the diluted PM 2.5 sample is not unexpected, as selenium is present in the gas phase at stack conditions (Germani and Zoller 1988;Galbreath et al 2000;Yan et al 2001). Selenium enrichment has been observed in Figure 1.…”
Section: Dilution and Pm 25 Compositionmentioning
confidence: 60%
“…Coal combustion is thought to be the main selenium releasing anthropogenic process, being responsible of about 7,300 tons of selenium per year (Yudovich and Ketris 2006). Selenium is one of the most volatile trace elements in coal, and is largely released in vapor phase to the atmosphere, mainly as the SeO 2 (g), SeO(g) and solid selenium species (Yan et al 2001). Haygarth et al (1994), demonstrated from selenium herbage historical data a positive correlation between the highest concentrations found in 1940 and 1970 with the high coal combustion activity observed in these years.…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…Selenium shows the greatest enrichment, with levels in the diluted sampling being as much as a factor of 12 than in the hot filters. The enrichment of selenium is not unexpected as it is known to be in the gas phase at stack conditions (Germani and Zoller 1988;Galbreath, Toman et al 2000;Yan, Gauthier et al 2001). In addition, enrichment of selenium has been observed in the plume downwind of a coal-fired power plant (Ondov et al 1989).…”
Section: Size Distributionsmentioning
confidence: 84%